2022
DOI: 10.1111/jam.15545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dosages of sodium butyrate and niacin on growth, faecal microbiota and Vitamin B metabolism in weaned piglets

Abstract: Aims Our study aimed to evaluate the effects of different dosages of sodium butyrate and niacin on the growth performance, faecal Vitamin B and microbiota in weaned piglets. Methods and Results Seventy‐two weaned piglets (Duroc × Landrace × Yorkshire, age of 21 days) were randomly assigned to one of six treatments (12 pigs/treatment); the control (CT) group was administered a basal diet. The groups in which concentration ratios of sodium butyrate to niacin were 100: 1, 100: 2, 100: 4, 100: 8 and 100: 16 (BN1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Consistent with the results of the present study, SB reduced serum urea nitrogen concentration in pigs (69, 70). GLU is a major source of energy for body tissues and cells, and serum levels of GLU are closely related to digestion and absorption (71). In the present study, serum GLU levels were found to be significantly higher in largemouth bass fed SB.…”
Section: Itemsupporting
confidence: 49%
“…Consistent with the results of the present study, SB reduced serum urea nitrogen concentration in pigs (69, 70). GLU is a major source of energy for body tissues and cells, and serum levels of GLU are closely related to digestion and absorption (71). In the present study, serum GLU levels were found to be significantly higher in largemouth bass fed SB.…”
Section: Itemsupporting
confidence: 49%
“…Previous studies have shown that niacin attenuates the severity of colitis by decreasing colonic MPO activity, TNF-α, and VEGF levels in a guinea pig model [ 27 ]. As a feed additive in animal husbandry, an increasing number of reports found that dietary niacin supplement significantly increased the relative abundance of probiotics in the colon, alleviating the inflammatory response in the small intestine [ 23 , 28 ], and increased the function of the intestinal epithelial barrier function [ 22 ]. However, little is known about the effect of niacin on the regulation of AQPs expression may be a potential target for the treatment of diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, the study using a reciprocal cross-fostering model revealed that the introduction of solid feed and weaning are more important determinants of gut bacterial succession in piglets than breed and nursing mother 28 . More studies have focused on the effects of specific dietary nutrients on the composition of gut microbiota, such as protein 29 , fibers 30 , 31 , vitamins 32 , 33 , sodium butyrate 33 , and some specific nutrient factors, e.g., soy isoflavone 32 and methylsulfonylmethane 34 . For example, low crude protein diet increased interaction network complexity, although it did not alter the microbial diversity 35 .…”
Section: Effects Of Non-genetic Factors On Pig Gut Microbial Composit...mentioning
confidence: 99%